Analisis Pengelolaan Keuangan Menggunakan Target Costing untuk Meningkatkan Laba pada Studio Foto Kamoe di Kota Jambi - Sartika, Siti; Syahrizal, Ahmad; Saputra, Ogi; Saputra, Hadi (Universitas Batanghari Jambi, 2026)
This study aims to analyze the application of the target costing method in financial management to increase profit at Studio Foto Kamoe in Jambi City, identify the challenges encountered, and examine its conformity with Islamic economic principles. The research employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation involving the owner, employees, and customersselected using purposivesampling. The results indicate that target costing is implemented through market price determination, profit targeting, and cost control during the planning stage, which improves cost efficiency and profit stability without compromising service quality. The main challenges include limited capital, rising rental costs, and suboptimal marketing strategies. From an Islamic economic perspective, the implementation of target costing reflects the principles of efficiency and justice (al-‘adl and ihsan), emphasizing fair pricing and social welfare. This study contributes to the development of Islamic financial management by demonstrating the relevance of target costing in the creative service sector as an efficient and ethical financial strategy.